Trend in Productivity research in Bangladesh Agriculture: A Review of selected Articles - Raihana, Bilkis (Asian Business Review, 2012)
This study is exploratory in nature. Changes in productivity in Bangladesh agriculture are issues of continuing research and policy interest. This article aims at interpreting the trends of productivity studies in Bangladesh agriculture sector including techniques, methods and models. This will be pursued on the basis of literature review of published books, journals and materials. Recent research developments in the study of productivity measurement have emphasized two things: the superiority of Total factor productivity (TFP) indexes and the use of flexible weight indexing procedures. But most of the earlier research work in Bangladesh agriculture has not incorporated both these approaches simultaneously. Efforts have been made to provide some recommendations to enhance the productivity studies in Bangladesh agriculture